Cover Picture: Electric‐Field Assisted In Situ Hydrolysis of Bulk Metal–Organic Frameworks (MOFs) into Ultrathin Metal Oxyhydroxide Nanosheets for Efficient Oxygen Evolution (Angew. Chem. Int. Ed. 31/2020). Issue 31 (22nd June 2020) - Tian, Jiayue; Jiang, Feilong; Yuan, Daqiang; Zhang, Linjie; Chen, Qihui; Hong, Maochun
Abstract : The ultrafast transformation of a bulk metal–organic framework (MOF) into ultrathin metal oxyhydroxide nanosheets for the oxygen evolution reaction (OER) through electric‐field hydrolysis is demonstrated by L. Zhang, Q. Chen, M. Hong et al. in their Research Article on page 13101 . The as‐prepared nanosheets exhibit excellent OER performance, and the evolution process from the bulk MOF into the metal oxyhydroxide nanosheets was investigated in detail.